Development of Graphene Oxide-Based Antibacterial Agents via ZnO/Eugenol Modification: Experimental and Computational Analysis - Karisma Triatmaja; Eko Sri Kunarti; Suyanta Suyanta; Priyagung Dhemi Widiakongko (Indonesian Journal of Chemistry)
The development of new antibacterial agents is proposed to solve the problem of drug-resistant bacterial strains caused by antibiotic misuse. The aim of this study was to improve the antibacterial activity by modifying graphene oxide (GO) using ZnO/eugenol and analyzing the interaction computationally. The study was started with GO synthesis using the modified Hummer method, followed by the dispersion of ZnO/eugenol through the mechanochemical method to GO to form GO/ZnO/eugenol composite. The composite was characterized using XRD, FTIR, UV-vis, SEM, and TEM. Results showed that the sonochemical method successfully prepared the GO/ZnO/eugenol composite. This material has better antibacterial E. coli activity than GO, with an inhibition zone of 11.5 mm in diameter, while pure GO showed no inhibition zone. MIC test presented that GO/ZnO/eugenol composite with 25 mg/mL suspension effectively prevented bacterial colony growth, while GO could only inhibit with 50 mg/mL suspension. Additionally, computational analysis through molecular docking suggested that the GO/ZnO/eugenol mechanism of action involves interference with DNA replication by hydrogenously interacting with the active site of DNA gyrase of E. coli bacteria. These findings highlight the potential of GO/ZnO/eugenol as a promising antibacterial agent for combating drug-resistant bacterial strains.